ADSORPTION KINETICS OF Pb(II), Cd(II) AND Cr(III) ON ADSORBENT PRODUCED BY PROTECTED-CROSSLINKING OF HUMIC ACID-CHITOSAN - Dewi Umaningrum; Uripto Trisno Santoso; Radna Nurmasari; Rahmat Yunus (Indonesian Journal of Chemistry, 2010)
Study on adsorption kinetics of of Pb(II), Cd(II) and Cr(III) on adsorbent which was produced by protected-crosslinking of humic acid-chitosan has been done. The Langmuir-Hinshelwood, pseudo first- and second-order kinetics models were used to describe the kinetic data, and the rate constants of adsorption were also evaluated. The experimental data fitted well the second-order kinetics model, indicating that the chemical sorption is the rate-limiting step, instead of mass transfer. The initial metal ion concentration significantly affects the adsorption rate. An increase in initial metal ion concentration results in the decrease in adsorption rate of the metals.